How Stereotype Threat and Stress Affect Learning: From Theory to Empirical Evidence - Aridah (LPPM Universitas PGRI Semarang, 2025)
Stereotype threat and stress are prevalent factors in education. Students experiencing one of these two psychological phenomena often demonstrate lower academic or learning performance. This article reviews and synthesizes some research findings, emphasizing on how stereotype threat and stress affect learning. It examines different domains, including science education such as mathematics and physics and second or foreign language learning. It also examines different demographic groups which include races, ethnic minority, gender and social class. By integrating theoretical perceptive with empirical evidence, this article offers a comprehensive overview of how stereotype threat and stress affect learning process and provides educators and parents with strategies of how to deal with threat and stress. The results of the analysis give some implications on learning in general and in language learning in particular.